Serum liquid biopsy for brain tumours: a scoping analysis of practicable approaches in low- and middle-income countries - Mohammad Hamza Bajwa; Muhammad Awais Khan; Faiza Urooj; Muhammad Usman Khalid; Syed Ather Enam; Hafiza Fatima Aziz; Kaynat Siddiqui; Muhammad Ehsan Bari; Nouman Mughal (Journal of the Pakistan Medical Association, 2024)
Approaches to brain tumour diagnosis and detecting recurrence after treatment are costly and significantly invasive. Developing peripheral-sample liquid biopsy tools is the key to enhancing our ability to prognosticate brain tumour subtypes and molecular heterogeneity. The present scoping review was designed to discuss current updates in liquid biopsy tools for diagnosis and guiding clinical management of brain tumours; we evaluated the literature within the context of low-and-middle-income country challenges. Circulating tumour cells (CTCs), circulating tumour DNA (ctDNA), cell-free DNA (cfDNA), extracellular vesicle-associated biomarkers, protein biomarkers, microRNAs, and serum metabolites are discussed with the collation of current data supporting their utility in liquid biopsy. Further challenges to implanting liquid biopsy tools at a systematic level are highlighted. Keywords: Tumour, DNA, Neoplastic Cells, Liquid Biopsy, Brain Neoplasms, MicroRNAs, Extracellular Vesicles